Latvijos ir Estijos požiūris į Klaipėdos atplėšimą nuo Lietuvos 1939 metais - Butkus, Zenonas; llmjärv, Magnus (Lietuvos istorijos studijos, 2009)
The article focuses on a topic that has never been tackled and constructively investigated in historiography. The issue of Klaipėda, which was one of the key international problems for Lithuania in interwar years, affected the international status and the stability of its northern neighbor countries, including other Baltic states - Latvia and Estonia. In 1923, having confirmed the annexation of Klaipėda region to Lithuania, they were both concerned that Lithuania would retain it, thereby preventing the historical German expansion from renewing in the northeast direction. In essence, the subject of Klaipėda did not prevent Lithuania from cooperating with Latvia and Estonia and from clustering into the Baltic Entente. This question did not belong to the "specific" problems pointed out in the peace treaty of the 12th of September 1934, which constituted an exception in the cooperation of the three Baltic countries.Latvia's backing of Lithuania in seeking to preserve Klaipėda is more tangible. The decision made by the Latvian government to transform the Consulate in Klaipėda into a General Consulate and to appoint Janis Seskis, a well-known politician and diplomat, as Consul is considered as support to Lithuania. The activity of the Latvian General Consul in Klaipėda was useful for Lithuania, giving the impression that not only Germany had exceptional rights in the Klaipėda region but that Latvia was also interested in it. The three-day visit of the Latvian navy to Klaipėda harbor (from the 5th to the 8th of August in 1935) is also considered as a beneficial action on the part of Latvia.Estonia's attempt to mediate in the argument between Germany and Lithuania over Klaipėda in 1938 by advising Lithuania to give Klaipėda to Germany by good will before they occupied it by force is not treated as an action directed against Lithuania either. That action was determined by the Estonian military and diplomatic office's belief that peace and stability could be preserved in Europe by satisfying Germany's ethnically-based territorial requirements. Estonian leaders also assumed that the most dangerous enemy of Estonia was the USSR, which could also be resisted with the help of Germany. Therefore, no Baltic country could afford to be in conflict with Germany.The loss of Klaipėda was considered by Estonia as an inevitable and imminent event, whereas Latvia treated it as a reprehensible fact of German expansion that Lithuania had to face and experience. Yielding Klaipėda did not stabilize the international status of Baltic countries but worsened it because the danger of USSR aggression became more intense, especially and primarily for Estonia and Latvia. This fact only indicates once more that the security of all three Baltic states is undivided.